2006
DOI: 10.1210/me.2005-0537
|View full text |Cite
|
Sign up to set email alerts
|

Single-Chain, Triple-Domain Gonadotropin Analogs with Disulfide Bond Mutations in the α-Subunit Elicit Dual Follitropin and Lutropin Activities in Vivo

Abstract: The human glycoprotein hormones chorionic gonadotropin (CG), TSH, LH, and FSH are heterodimers composed of a common alpha-subunit and a hormone-specific beta-subunit. The subunits assemble noncovalently early in the secretory pathway. LH and FSH are synthesized in the same cell (pituitary gonadotrophs), and several of the alpha-subunit sequences required for association with either beta-subunit are different. Nevertheless, no ternary complexes are observed for LH and FSH in vivo, i.e. both beta-subunits assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The gonadotrope-targeted hFSH β transgene rescued Fshb null male and female mice, and ectopically produced hFSH rescued null males but only partially rescued female Fshb null mice [25]. These mice have been extensively used later on in collaborative studies with Dr. Irving Boime, to test the bioactivities of various gonadotropin analogs [26, 27]. …”
Section: Applications Of Fshβ Ko Modelmentioning
confidence: 99%
“…The gonadotrope-targeted hFSH β transgene rescued Fshb null male and female mice, and ectopically produced hFSH rescued null males but only partially rescued female Fshb null mice [25]. These mice have been extensively used later on in collaborative studies with Dr. Irving Boime, to test the bioactivities of various gonadotropin analogs [26, 27]. …”
Section: Applications Of Fshβ Ko Modelmentioning
confidence: 99%
“…76,77 Subsequently, similar fusion proteins of LH and FSH were also found to be bioactive. [82][83][84] The single chain hormones also displayed increased stability and heat resistance in vitro compared to their heterodimeric counterparts. 80,81 From these studies it was concluded that the N-α-hCGβ-C configuration was also bioactive and, quite surprisingly, that, each disulfide of the subunits could be eliminated without a loss of activity.…”
Section: Protein Engineeringmentioning
confidence: 99%
“…90 A second single chain hCG antagonist was designed by mutating three of the four N-linked glycosylation sites that are associated with LHR activation (Asn 13 and 30 in the β subunit and Asn 52 in the α subunit). A most provocative finding was based on a bifunctional, triple domain fusion protein of the form: N-FSHβ-hCGβ-α-C. 84 These investigators showed that disruption of heterodimer formation by mutation of either Cys10-Cys60 or Cys32-Cys84 did not eliminate bioactivity, and thus concluded that αβ contacts are not required for receptor binding and activation. This analog behaved as a competitive antagonist and suppressed ovarian hyperstimulation syndrome in rats.…”
Section: Protein Engineeringmentioning
confidence: 99%
“…Those analyses used polyclonal antisera to FSH/FSH␤. Here we used a high affinity FSH dimerspecific monoclonal antibody (23,24) to identify the proteins because it does not cross-react with the uncombined FSH␤ subunit, thus reducing the background. As shown previously, the ␣ and FSH␤ subunits migrate at similar rates on SDS gels, and their resolution is not clear (21).…”
Section: Secretion Of Lh and Lh⌬t After Steady-statementioning
confidence: 99%